The Free School Triumph in London, Canada West, 1840 to 1852: An Urban First - Murphy, Michael (Ontario History)

(untitled) (The Ontario Historical Society, 2018)
Grant-aided common schools in Canada West went free between 1850 and 1870. This article attempts to answer why by studying London between 1840 and 1852. It explains how citizens, the power structure, and schools intersected prior to 1850 to marginalize the community’s common schools and most youngsters and to privilege others. It will demonstrate how the centre’s changing character and the Reform impulse (writ both large and small, but reflected in this colony by new laws in 1849-50 covering not only education but also municipal, elections, and assessment matters), transformed education arrangements, bringing almost all school-age children immediately into its now ascendant free, comprehensive common schools.